DECOLORIZATION OF BROMOCRESOL PURPLE (BCP) PHOTOINDUCED BY A Fe (III) OXYHYDROXYDE (GOETHITE) (Sciences & Technology. A, exactes sciences, 2014)
This study focused on the decolorization of bromocresol purple (BCP) using Fe (III) oxyhydroxide (Goethite) as an inducer. The mixture dye- Goethite in dark condition and ambient temperature, shows a reaction between the dye and the Fe (III) oxyhydroxide. Indeed, the tracking of the reaction using UV-visible spectrophotometry showed a low decrease in the principal band of the dye. This reveal the existence of an interaction between the substrate and the Goethite whitch is important in acidic medium. The irradiation at 365 nm of mixture Goethite-BCP (1g.L-1- 10-4 M) leads to a transformation of substrate. The decrease of the band at 432nm and the presence of an isosbestic point at 508 nm support the transformation of BCP.  The substrate kinetics disappearances are improved in acidic medium. The addition of hydrogen peroxide (5.10-3 mol.L-1) in a suspension of Goethite, accelerate significantly the rate of disappearance of the dye. Natural radiation tests showed that the degradation was faster than artificial one at 365 nm. Studies on mineralization using COD method certify that this method, compatible with the environment, may be considered in the treatment of wastewater.